2018
DOI: 10.1093/humrep/dey281
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a thin endometrial lining on fresh and frozen–thaw IVF outcomes: an analysis of over 40 000 embryo transfers

Abstract: STUDY QUESTIONDoes each millimeter decrease in endometrial thickness lead to lower pregnancy and live birth rates in fresh and frozen IVF cycles?SUMMARY ANSWERClinical pregnancy and live birth rates decline as the endometrial thickness decreases below 8 mm in fresh IVF-ET and below 7 mm in frozen–thaw embryo transfer (ET) cycles.WHAT IS KNOWN ALREADYPrevious studies have been heterogenous and have shown conflicting results on the impact of endometrial thickness on IVF outcomes. Most studies do not include many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
173
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 250 publications
(181 citation statements)
references
References 14 publications
5
173
0
3
Order By: Relevance
“…Previous studies reported that pregnancy rates after ET are reduced when the EMT on the day of transfer (ie, in the secretary phase) is ≤7−8 mm . In the present study, ETs were performed in patients with an EMT ≥8 mm on the day of ET, as based on previous reports, it is highly likely that the endometrium would be receptive to embryo implantation.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Previous studies reported that pregnancy rates after ET are reduced when the EMT on the day of transfer (ie, in the secretary phase) is ≤7−8 mm . In the present study, ETs were performed in patients with an EMT ≥8 mm on the day of ET, as based on previous reports, it is highly likely that the endometrium would be receptive to embryo implantation.…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies reported that pregnancy rates after ET are reduced when the EMT on the day of transfer (ie, in the secretary phase) is ≤7−8 mm. 4,7 In the present study, ETs were performed in patients with an EMT ≥8 mm on the day of ET, as based on previous reports, it is highly likely that the endometrium would be receptive to embryo implantation. However, the present study results demonstrate that the EMT on the day of trigger is more tightly associated with pregnancy outcomes than is the EMT on the day of ET in CC-based minimal stimulation cycles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Between 15 and 25 the decision was left up to the gynaecologist who performed the OPU. FA policy was also applied for: -Uterine anomalies detected during ovarian stimulation (de Ziegler et al 2016;Tsiami et al 2016;liu et al, 2018) which includes endometrial, myometrial, or tubal anomalies -progesterone levels superior to 1.5ng/ml on the day of ovulation triggering (Lawrenz et al,2017;Asada Y. et al, 2019;Vuong L. N. et al, 2019).…”
Section: Embryo Culture Cryopreservation and Thawingmentioning
confidence: 99%